Does it matter what children read? New evidence using longitudinal census data from Spain - Jerrim, John; López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Taylor & Francis, 2020)
It has long been thought that encouraging children to read is likely to bebeneficial for the development oftheir literacy skills. However, a lot less attention has been paid to the issue of whether what students read matters for their academic progress. This paper there fore considers the association between the frequency young peo ple read five different types of text (comics, short stories, books, newspapers and magazines) and their scores on standardised read ing and mathematics tests. Drawing upon large longitudinal census data from the largest administrative region in Spain, we find that frequency of reading comics, newspapers and magazines is not associated with the development of children’s cognitive skills. In contrast, there is clear and consistent evidence of a positive and increasing association between the frequency children read books and their academic achievement. We consequently conclude that recommended reading time for children should be focused upon the time they spend reading books and not other material.
https://openpolicyfinder.jisc.ac.uk/id/publication/5915
Keywords: Lectura - Estudio y enseñanza; Comprensión lectora; Books; Short novels; Reading skills; Primary education; Secondary education